Association between adherence to iron intake and anaemia prevalence among women in Cambodia and India: new evidence from recent global demographic and health surveys - Raut, Manoj Kumar; Reddy, J. C.; Rahman, Md. Ataur (International Journal Of Community Medicine And Public Health, 2018)
Background: Anaemia is a global public health problem affecting around 800 million children and women worldwide. Anaemia, defined as a reduced haemoglobin concentration, is associated with increased peri-natal mortality, increased child morbidity and mortality, impaired mental development, impaired immune competence, increased susceptibility to lead poisoning, and decreased performance at work. Methods: This paper attempts to understand the determinants underlying iron and folic acid intake and correlates of anaemia prevalence in two countries in the Asia region using multivariate binary logistic regression analyses of recent data from the Demographic and Health Surveys of Cambodia and India. The individual level data was analysed, using Predictive Analytics Software for Windows (PASW) 18.0 release. Results: After adjusting for standard co-variates, reading newspaper and watching television was significantly associated with coverage, while reading newspaper and listening to radio was significantly associated with adherence to iron tablets or syrup in India. In case of both Cambodia and India, those who received at least three antenatal care visits were much more likely to adhere to at least 90 days of iron tablet or syrup or iron and folic acid tablets, more so in Cambodia compared to India. Those who reported to have adhered to at least 90 days of iron and folic acid tablets in India were more likely to be not anaemic unlike in case of Cambodia. Conclusions: Antenatal care-seeking visits seem to be a particularly effective ways of reaching women and in increasing the likelihood of intake of iron only or iron and folic acid supplements.